In vivo characterization of polymer based dental cements - Widiyanti P; Siswanto Siswanto (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: In vivo studies investigating the characterization of dental cements have been demonstrated. As few in vitro studies on this cement system have been performed. Previous researches in dental material has been standardized dental cement which fulfilled the physical and mechanical characteristic such as shear strength but were on in vitro condition, the animal model and clinical study of dental cement from laboratory has not been done yet. This research examined physical and mechanical characteristic in vivo using rabbit by making the caries (class III) in anterior teeth especially in mesial or distal incisive, fulfilled the cavity by dental cement and analyzed the compressive strength, tensile strength, and microstructure using scanning electron microscope (SEM). Purpose: This study is aimed to describe the in vivo characterization of dental cements based on polymer (zinc phosphate cement, polycarboxylate, glass ionomer cement and zinc oxide eugenol). Methods: First, preparation was done on animal model’s teeth (6 rabbits, male, 5 months old). The cavity was made which involved the dentin. Then the cavity was filled with dental cement. After the filling procedure, the animal model should be kept until 21 days and than the compressive test, tensile test and microstructure was characterized. Compressive test and tensile test was analyzed using samples from extracted tooth and was measured with autograph. The microstructure test was measured using SEM. Results: The best compressive strength value was belongs to zinc phosphate cement which was 101.888 Mpa and the best tensile strength value was belongs to glass ionomer cement which was 6.555 Mpa. Conclusion: In conclusion, comparing with 3 others type of dental cements which are zinc phosphate, polycarboxylate and glass ionomer cement, zinc oxide eugenol cement has the worst for both physical and mechanical properties.Latar belakang: Studi in vivo meneliti karakterisasi secara in vivo dari semen gigi. Beberapa studi in vitro di bidang ini telah dilakukan. Beberapa riset di bidang material gigi telah menghasilkan semen gigi yang memenuhi standart sifat fisik dan mekanik seperti regangan dan kekuatan secara in vitro, sedangkan uji in vivo dan uji klinis dari semen gigi dari laboratorium belum dilakukan. Penelitian ini menguji karakteristik fisik dan mekanik semen gigi menggunakan hewan coba kelinci dengan membuat karies kelas III di gigi anterior terutama di permukaan mesial atau distal insisif, mengisi kavitas dengan semen gigi dan menganalisa kekuatan tekan, kekuatan tarik dan struktur mikronya dengan menggunakan scanning electron microscope (SEM). Tujuan: Studi ini bertujuan memberikan gambaran karakterisasi in vivo semen gigi berbahan dasar polimer (semen seng fosfat, polikarboksilat, ionomer kaca dan seng oksida eugenol). Metode: Pertama, kami melakukan preparasi pada gigi hewan coba (6 kelinci, jantan, usia 5 bulan). Kemudian kita membuat kavitas yang melibatkan dentin. Lalu kami menumpat kavitas dengan semen gigi. Setelah prosedur penumpatan, hewan coba dipelihara selama 21 hari dan dikarakterisasi kekuatan tekan, kekuatan tarik dan struktur mikronya. Kekuatan tekan dan kekuatan tarik dianalisa dari sampel uji gigi hewan coba yang diekstraksi dan diukur dengan autograf. Struktur mikronya diuji dengan SEM. Hasil: Hasil nilai kuat tekan terbaik diperoleh oleh semen seng fosfat (zinc phosphate cement) sebesar 101,888 Mpa dan nilai kuat tarik semen gigi terbaik adalah semen gelas ionomer (glass ionomer cement) sebesar 6,555 Mpa. Kesimpulan: Dapat disimpulkan, dari ketiga jenis bahan semen yaitu seng fosfat, polikarboksilat, dan ionomer kaca, yang mempunyai sifat fisik dan mekanikal terburuk adalah semen ionomer kaca.